Trends and Gaps in Clinical Research on Tooth Bleaching: A Bibliometric Analysis of Studies Published From 2001 to 2024 - Aragão, Walessa Alana Bragança; Chemelo, Victória Santos; Melo, Wallacy Watson Pereira; Gomes‐Moura, José Lucas; Loretto, Sandro Cordeiro; Lobato, Marcelo Figueiredo; Souza‐Rodrigues, Renata Duarte; Reis, Alessandra; Loguercio, Alessandro Dourado; Lima, Rafael Rodrigues (Journal of esthetic and restorative dentistry, 2025)
ABSTRACT Introduction The objective of this bibliometric review is to address the main trends and development in dental whitening throughout the 21st century, as well as to identify knowledge gaps on the subject. Method A search was conducted in the Web of Science Core Collection database and information was extracted regarding the journal, authors, keywords, year of publication, number of citations, country, continent of the corresponding author. After reading the articles, data such as study design, type of bleaching technique, types of light sources used with the bleaching, occurrence of tooth sensitivity, and tooth color change analysis method were extracted. Results The journal with the largest number of publications was “Operative dentistry” (n = 61), and the authors with the most articles were Loguercio AD (n = 82) and Reis A (n = 76). The productions are concentrated in Brazil, with emphasis on the State University Ponta Grossa. Most of the articles are randomized clinical studies that used the in‐office bleaching technique with 35% hydrogen peroxide. Conclusion Our results show that the most recent studies used light sources such as a violet LED during whitening; however, more studies are needed to prove the benefits in relation to color change and reduction of tooth sensitivity.